1986
DOI: 10.1111/j.1600-0765.1986.tb01470.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological investigation of various forms of inflammatory periodontitis

Abstract: Antibody levels towards sonicated wbole eel! extracts of selected oral Gram negative bacteria and Actinomyces viscosus were determined in sera from patients with various inflammatory forms of periodontal disease and from healthy control individuals. Antibody titres to two (non-leukotoxin producing) strains of Actinobacillus actinomycetemcomitans were significantly elevated in patients with juvenile periodontitis. Adult patients with severe periodontitis had significantly lower IgG antibody titres to Veillonell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…A strong local and systemic antibody response to A. actinomycetemcomitans has been adduced as an indicator of localized early-onset periodontitis (6,12,326). An association between the most severe and extensive cases of generalized early-onset periodontitis and the relative lack of antibodies to P gingivalis and/or A. actinomycetemcomitans has also been reported (114,134). This, coupled with the previously quoted findings that humoral responsiveness in generalized earlyonset periodontitis in terms of antibody avidity is depressed compared with that found in adult periodontitis patients and healthy individuals, suggests possible disease mechanisms.…”
Section: The Host Response In Differentiation Of Disease Statesmentioning
confidence: 99%
“…A strong local and systemic antibody response to A. actinomycetemcomitans has been adduced as an indicator of localized early-onset periodontitis (6,12,326). An association between the most severe and extensive cases of generalized early-onset periodontitis and the relative lack of antibodies to P gingivalis and/or A. actinomycetemcomitans has also been reported (114,134). This, coupled with the previously quoted findings that humoral responsiveness in generalized earlyonset periodontitis in terms of antibody avidity is depressed compared with that found in adult periodontitis patients and healthy individuals, suggests possible disease mechanisms.…”
Section: The Host Response In Differentiation Of Disease Statesmentioning
confidence: 99%
“…A correlation between specific antibacterial antibody titles and the various forms of periodontal disease has been examined previously. Although elevated serum antibody titres were described by many authors (4,14,16,24) normal antibody levels (18,19) or even decreased antibody titres (3,4,12) have been also reported in patients with periodontitis when compared with healthy controls. One of the major difficulties in evaluating the antibody response in periodontal disease has been the antigenic complexity of periodontopathic bacteria.…”
mentioning
confidence: 98%
“…Until recently, studies of the IgG subclasses in the serum from patients with periodontitis have reported that there were no detectable differences in the total subclass levels between patients with adult periodontitis (AP) (Mackler et al 1979;Reinhardt et al 1989), localised juvenile periodontitis (LJP) (Waldrop, Mackler & Schur 1981) and control subjects without either disease. Farida et al (1986) have estimated the levels of specific anfibodies to the whole cell extracts of P. gingivalis in patients with AP and LJP. They found that the IgG2 subclass levels were highest in patients with LJP but that patients with AP had IgG2 and IgGl antibodies in equal proportions.…”
mentioning
confidence: 99%